Neutrosophic model for Analyzing the Effect of the Enterprise Resource Planning Functions on Business Processes - Samah Ibrahim Abdel aal; Mahmoud M. A. AbdEllatif (Neutrosophic Sets and Systems)
In today's dynamic business environment, we seek to improve the efficiency of decision-making and operational processes by implementing the Enterprise Resource Planning (ERP) systems. The ERP systems provide an integrated database with a single platform that supports various functional areas of the organization for improving the management of business processes. The implementation of the ERP system requires understanding the effect of each function of the ERP system on Business Processes (BP) to maximize its use. Most studies have looked at critical success factors that help ERP systems succeed and other related issues, but they haven't examined how each ERP function impacts business processes. There are several studies that have addressed the ERP systems and different aspects of them, especially the successful implementation of the ERP systems; the ERP systems offer many functions and features that can help different areas within organizations. So, it's important to examine how these functions impact various parts of the organization. This will help improve their use and address any issues. This work intends to address the ERP systems with various aspects and their functions. Also, this work aims to introduce a neutrosophic model for analyzing the effect of the ERP functions on business processes. This work utilizes the neutrosophic numbers to handle uncertainty during the analyzing process. The proposed model considers the cost and benefits during the analysis of the effect of each function on BP. The proposed model was tested in a case study, and the results showed that it is an effective and straightforward new method for dealing with uncertainty. It considers costs and benefits during analysis, providing a clear understanding of how each part of the ERP system affects Business Processes.